New Straits Times, 28 August 2009 - Suzieana Uda Nagu (The New Straits Times Press (M) Bhd, 2009)
In Australia, intermitten showers in June signal the coming of winter. Wet spells are certainly welcomed in the driest inhabited continent of Earth , which is facing drier climate and rising demand for water.